2004
DOI: 10.1111/j.1365-2362.2004.01387.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of cholesterol ester of apolipoprotein B100‐containing lipoproteins in dogs: evidence for disregarding cholesterol ester transfer

Abstract: These kinetic data showed that VLDL cholesterol ester and LDL cholesterol ester metabolism followed VLDL and LDL apoB100 metabolism, and that consequently there is no in vivo transfer of cholesterol ester in dogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 44 publications
2
10
0
Order By: Relevance
“…As well, TG‐enrichment of HDL could be related to the higher apo A‐I FCR observed, because triglycerides‐enriched HDL is a better substrate for hydrolysis by hepatic lipase [13]. However, effects of TG‐enrichment on HDL metabolism have been described in human studies and are related to a higher CETP activity with increased pool of VLDL‐TG [6]. Given that CETP activity is not detectable in healthy and insulin resistant dogs, investigations are needed to demonstrate the mechanism of TG‐enrichment and its effect on HDL metabolism in dog.…”
Section: Discussionmentioning
confidence: 99%
“…As well, TG‐enrichment of HDL could be related to the higher apo A‐I FCR observed, because triglycerides‐enriched HDL is a better substrate for hydrolysis by hepatic lipase [13]. However, effects of TG‐enrichment on HDL metabolism have been described in human studies and are related to a higher CETP activity with increased pool of VLDL‐TG [6]. Given that CETP activity is not detectable in healthy and insulin resistant dogs, investigations are needed to demonstrate the mechanism of TG‐enrichment and its effect on HDL metabolism in dog.…”
Section: Discussionmentioning
confidence: 99%
“…Dogs are known to show a large variability in plasma cholesterol and TG (Wolfgang et al, 1995;Bailhache et al, 2004). The three dogs enrolled in this study showed different lipid concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…The SAAM II program (version 1.0.1; Resource Facility for Kinetic Analysis, Department of Bioengineering, SAAM Institute, Seattle, WA) was used to fit the model to the observed tracer data by a weighed least-squares approach to find the best fit as previously described (Maugeais et al, 2001;Bailhache et al, 2004) and to determine the parameters of the model. In brief, as described previously (Maugeais et al, 2001;Bailhache et al, 2004), such approach started with the simplest model based on minimal assumptions (i.e., apoB100 enters plasma through secretion of VLDL, which is then converted into LDL by triglyceride lipolysis, which would represent lipoprotein lipase activity). The complexity of the model was then progressively increased by including more known or credible physiological details until the optimal complexity was reached.…”
Section: Kinetic Studiesmentioning
confidence: 99%
“…1), as previously described [25]. Briefly, tracer-to-tracee ratio of plasma free leucine was used as a forcing function describing the input of labeling into the system.…”
Section: Modelingmentioning
confidence: 99%